SLOPE HANDLING DESIGN PIHANIN BRIDGE PANDAN SARI VILLAGE HULU SUNGAI SELATAN REGENCY - Markawie Markawie; Achmad Abdurrahman (Universitas Lambung Mangkurat, 2018)
The road leading to the village of Pandan Sari, Hulu Sungai Selatan Regency, is one of the important infrastructures for the community's economy in the village of Pandan Sari. The occurrence of landslides causes the transportation line to be cut off so that it needs to be repaired, the construction used to replace the road is a slab pile bridge because the implementation is quite easy and the construction costs are relatively cheap. This bridge has a 86 m span with the bridge class is a special class C with a traffic width of 5.5 m and a sidewalk of 0.25 m. The purpose of this final project is to obtain a construction design that is safe, qualified and economical in its manufacture.This design includes planning the upper structure, lower structure, and bridge foundation. Where the imposition of upper and lower building structures refers to RSNI T-02-2005, Calculation of loading is assisted by using SAP2000 software. Floor plate planning uses the Bittner method and the plate is considered as a 1 m wide beam. So that the biggest styles are used between the two methods. Quality specifications of U-32 main reinforcement steel (fy 320 MPa) quality of U-24 divider and shear reinforcement steel (fy 240 MPa). On the slab used concrete with fc '35 MPa quality. Whereas on the back and lower structure concrete is used with fc '30 MPa quality). Then proceed with analysis of slope stability against safety factors in conditions before and after the reinforcement.From the calculation results obtained 25 cm floor plate design D19-80 main reinforcement and divider reinforcement Ø16-100. In the abutment foundation, used manufacturing poles in the form of PC class B spun pile 30 cm in diameter as many as 12 poles, for 4 slab pile slabs (voute 1), and 6 poles per transverse beam (voute 2) ) Obtained bearing capacity (757.64 kN)> pile style (181.41 kN) and lateral carrying capacity (250.870 kN)> lateral force (95.76 kN). SF (Safety Factor) obtained before the reinforcement is 0.983 and after the strengthening is obtained 2.684.Keywords: Bridge, reinforced concrete, pile slab, abutment, pile.